2011
DOI: 10.3111/13696998.2011.554932
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of atazanavir-ritonavir versus lopinavir-ritonavir in treatment-naïve human immunodeficiency virus-infected patients in the United States

Abstract: By more effectively reducing viral load with less gastrointestinal toxicity and a better lipid profile, ATV + r lowered rates of AIDS and CHD, increased quality-adjusted survival, and was cost effective (< $50,000/QALY) compared with LPV/r.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 32 publications
2
21
1
2
Order By: Relevance
“…Others 19 have compared the economic impacts of LPV/r and ATVþRTV in ART-naïve patients and found estimates that differ greatly from the ones identified by our model. An economic study utilizing the 96-week CASTLE data to compare the economics of LPV/r and ATVþRTV concluded that the ATVþRTV regimen is superior.…”
Section: Discussioncontrasting
confidence: 71%
“…Others 19 have compared the economic impacts of LPV/r and ATVþRTV in ART-naïve patients and found estimates that differ greatly from the ones identified by our model. An economic study utilizing the 96-week CASTLE data to compare the economics of LPV/r and ATVþRTV concluded that the ATVþRTV regimen is superior.…”
Section: Discussioncontrasting
confidence: 71%
“…The Markov microsimulation model devised by Broder et al [12] was further refined to create a new model (Fig. 1) from the NHS payer’s perspective that included direct costs and health outcomes of Italian HIV-infected patients receiving ATV+r or LPV/r.…”
Section: Methodsmentioning
confidence: 99%
“…This predictive model was used to analyze the results of the CASTLE study (an open-label international non-inferiority randomised study of the use of LPV/r vs. ATV+r in antiretroviral-naïve HIV-1-infected patients) [11], in terms of quality-adjusted life years (QALY) related to the patients’ health states and the associated costs. A later study [12] applied the Markov microsimulation model (based on the individual patient level) to HIV-infected patients in accordance with the most recent international guidelines on drug treatment and patients evaluation (e.g., using 8 instead of 12 health states), rate of opportunistic infections (OIs), AIDS diagnosis, coronary heart disease (CHD) events, and incidence of hyperbilirubinemia and diarrhoea.…”
Section: Introductionmentioning
confidence: 99%
“…Standard care 190,000 (low risk with uterus) 100,000 72,000 (low risk without uterus) 57,000 (high risk with uterus) 37,000 (high risk without uterus) Breast cancer 20 Adjuvant trastuzumab Standard care 39,000 N/A Breast cancer 21 Anastrozole Tamoxifen 26 OnabotulinumtoxinA Best supportive care 24,000 N/A Knee osteoarthritis 27 Disease-modifying osteoarthritis drugs Standard care 57,000 N/A Chronic low back pain 28 Duloxetine Naproxen 59,473 N/A Human immunodeficiency virus 29 Generic-based antiretroviral therapy No antiretroviral therapy 21,000 100,000 Branded antiretroviral therapy Generic-based antiretroviral therapy 114,000 Type 2 diabetes 30 Exenatide Insulin glargine 15,000 N/A ADHD 31 Guanfacine XR + stimulant Stimulant monotherapy 31,000 50,000 Anticoagulation in cancer patients 32 Low molecular-weight heparin No prophylaxis 90,893 N/A Stroke prevention in atrial fibrillation 33 Rivaroxaban Warfarin 27,000 100,000 Multiple sclerosis 34 Fingolimod IFN beta-1a 73,000 100,000 S. aureus vaccine in hemodialysis patients 35 Vaccine (1% colonization rate) No vaccine 25,217 N/A Schizophrenia 36 Olanzapine ODT SOT 19,000 N/A Olanzapine ODT Risperidone SOT 39,000 End-stage renal disease 37 Erythropoietin stimulating agents Routine blood transfusions 873 N/A Hyperlipidemia 38 Atorvastatin Simvastatin 45,000 N/A Acute coronary syndrome 39 Ticagrelor Genotype-driven treatment 10,000 50,000 Human immunodeficiency virus 40 Atazanavir -ritonavir Lopinavir -ritonavir 26,000 50,000 Type 2 diabetes 41 Liraglutide Exenatide 40,000 N/A Human immunodeficiency virus 42 Darunavir -ritonavir Lopinavir -ritonavir 23,000 N/A Macular degeneration 43 Bevacizumab Ranibizumab -54,000 N/A Cardiovascular disease 44 Rosuvastatin (20-year horizon) Placebo 10,000 N/A Rosuvastatin (10-year horizon) 44 …”
Section: Tamoxifenmentioning
confidence: 99%